Relative deprivation in the labor market - Paolo Verme (IZA World of Labor, 2017)
Why do different population groups (e.g. rural vs. urban, youth vs. elderly and men vs. women) experience the same objective labor status differently? One hypothesis is that people are more concerned with relative deprivation than objective deprivation and they value their own status relative to the status of their peers—the reference group. One way to test this hypothesis in the labor market is to measure individual differences in labor status while controlling for characteristics that define population groups. This measure is called “relative labor deprivation” and can help policymakers to better understand how labor claims are generated.
Keywords: H3; I3; J2; J4; J7; 330; objective deprivation; subjective deprivation; unemployment; social discontent